2019
DOI: 10.3389/fnbeh.2019.00081
|View full text |Cite
|
Sign up to set email alerts
|

Erroneously Disgusted: fMRI Study Supports Disgust-Related Neural Reuse in Obsessive-Compulsive Disorder (OCD)

Abstract: Objective : fMRI scans of patients with obsessive-compulsive disorder (OCD) consistently show a hyperactivity of the insular cortex, a region responsible for disgust-processing, when confronted with symptom-triggering stimuli. This asks for an investigation of the role of disgust and the insula in OCD patients. Methods : Seventeen inpatients with OCD and 17 healthy controls (HC) underwent fMRI scanning. Whole-brain contrasts were calculated for “Disgust vs. Neutral” for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Although the current study was conducted-for clear ethical reasons-on a sample of nonpathological individuals, results have potential implications for the treatment of OCD. As described previously, evidence suggests that disgust and deontological morality play a pivotal role in the genesis and maintenance of OCD and points to the role of the insula as one of the putative neural substrates underlying these constructs (e.g., for deontological guilt, see Basile et al, 2014; for disgust, see Viol et al, 2019). In light of this, Buyukturkoglu and colleagues ( 2015 straightforward conclusions from a study with such a limited number of participants is not advisable, this is a remarkable example of how down-regulation of a brain region represents a clinical method for promising treatments.…”
Section: Discussionmentioning
confidence: 69%
“…Although the current study was conducted-for clear ethical reasons-on a sample of nonpathological individuals, results have potential implications for the treatment of OCD. As described previously, evidence suggests that disgust and deontological morality play a pivotal role in the genesis and maintenance of OCD and points to the role of the insula as one of the putative neural substrates underlying these constructs (e.g., for deontological guilt, see Basile et al, 2014; for disgust, see Viol et al, 2019). In light of this, Buyukturkoglu and colleagues ( 2015 straightforward conclusions from a study with such a limited number of participants is not advisable, this is a remarkable example of how down-regulation of a brain region represents a clinical method for promising treatments.…”
Section: Discussionmentioning
confidence: 69%
“…This result is consistent with both the studies stating that disgust is an important feeling in vaginismus patients and the studies suggesting that insula plays a role in the neurobiology of disgust. 9,18 Another important point is the fact that impairment in insula was detected in Cho and mIns metabolites. Cho is required for the synthesis and secretion of acetylcholine, 19,20 which is a critical neurotransmitter that mediates memory storage.…”
Section: Discussionmentioning
confidence: 99%
“…8 Its neurobiology has been investigated especially in OCD patients dwelling on the role of insular cortex. 9 A functional imaging study reported that insular cortex is activated as a response to disgust in both healthy participants and OCD patients. 10,11 Considering that disgust is a factor that makes treatment difficult, it can be thought that metabolic disorder of the insular cortex may be important role at response to group therapy in vaginismus patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is especially with regard to sexual matters that women are more easily disgusted than men (Sparks et al 2018 ). A side effect of the difference in disgust between the sexes appears to be that women suffer more than men from disgust-related mental problems like obsessive-compulsive disorder, eating disorders, and animal phobias (Al-Shawaf et al 2018 ; Amoroso et al 2020 ; see also Viol et al 2019 ).…”
Section: The Benefit Of Procreation Against the Cost Of Infectionmentioning
confidence: 99%